2020
DOI: 10.3390/d12040126
|View full text |Cite
|
Sign up to set email alerts
|

Hummingbird–Plant Interactions Are More Specialized in Forest Compared to Coffee Plantations

Abstract: Deforestation transforms habitats, displacing vertebrates and the other dimensions of biodiversity they support through their interactions. Few empirical studies have quantified the effect deforestation has on vertebrate–pollinator interaction networks. Here we quantify how hummingbird–plant networks change in relation to hummingbird diversity across a deforestation gradient. We found that, overall, hummingbird–plant interactions were significantly more specialized in forests and specialized interactions decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
(95 reference statements)
1
13
0
Order By: Relevance
“…This specialization can be related to flower morphology (Fonseca et al., 2016; Maglianesi et al., 2014) and to hummingbird morphology (beak length) (Maglianesi et al., 2014). However, it was shown that hummingbirds relaxed their specialized relationships and became less specific in their interactions in nonforested areas (Morrison & Mendenhall, 2020). Our research was conducted in a Campo Rupestre area, where trees are rare; so, our result of a lower specialization in our interaction network was expected.…”
Section: Discussionmentioning
confidence: 99%
“…This specialization can be related to flower morphology (Fonseca et al., 2016; Maglianesi et al., 2014) and to hummingbird morphology (beak length) (Maglianesi et al., 2014). However, it was shown that hummingbirds relaxed their specialized relationships and became less specific in their interactions in nonforested areas (Morrison & Mendenhall, 2020). Our research was conducted in a Campo Rupestre area, where trees are rare; so, our result of a lower specialization in our interaction network was expected.…”
Section: Discussionmentioning
confidence: 99%
“…In forest fragments around Coto Brus, mismatched hummingbirds account for c.a. 10% of honest visits (those in which the visitor contacts the reproductive organs of the flower) to H. tortuosa (K. Leimburger, unpublished data ), but this proportion likely increases in isolated fragments where morphologically matched hummingbirds are less common [3436]. The combination of fragmentation and pollinator recognition therefore has a strong ecological impact on H. tortuosa populations, which show reduced seed sets in fragmented forests compared to those in continuous forest [37], presumably due to a paucity of morphologically matched hummingbirds.…”
Section: Discussionmentioning
confidence: 99%
“…This specialization can be related to the flower morphology (Maglianesi et al 2014, Fonseca et al 2016) and to hummingbird morphology (beak length) (Maglianesi et al 2014). However, it was shown that hummingbirds relaxed their specialized relationships and became less specific in their interactions in non-forested areas (Morrison and Mendenhall, 2020). Our research was conducted in a Campo Rupestre area, where trees are rare, reinforcing our result of a lower specialization in our interaction network.…”
Section: Discussionmentioning
confidence: 99%